Composite Culture in a Multicultural Society - Chandra, Bipan; Mahajan, Sucheta (Pearson, 2006)
The book comprises contributions from the fields of political theory and philosophy; ancient, medieval and modern history; sociology; anthropology and creative arts. It provides perspectives drawing on the multicultural experiences of the United States, Britain, Trinidad, Pakistan and Malaysia and includes experience of composite culture in the ancient, medieval and modern periods of Indian history. There are essays on the contemporary experience of multiculturalism in India. It covers social sciences, international relations, cultural studies, international migration and diasporic communities.